Efektivitas Tagline #DijaminOri terhadap Brand Awarness E-Commerce JD.ID - Widyastuti, Dominica A.; Nugroho, Muhammad Rizky (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This study aims to analyze the effectiveness of the #dijaminOri tagline used by JD.ID companies to establish their brand awareness. In testing this study a questionnaire was used with 10 items of statements distributed to 100 respondents. The sample used in this study were people who had seen the #DijaminOri tagline. The sample is done by purposive sampling method. In this study simple regression analysis was used. The results of this study indicate that the tagline has a very significant effect with a positive direction.